1998
DOI: 10.1073/pnas.95.14.8199
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic selection of NK1.1+α/β T cell antigen receptor (TCR)+cells in transgenic mice bearing TCR specific for chicken ovalbumin and restricted to I-Ad

Abstract: A BSTR ACTGeneration and negative selection of NK1.1 ؉ ␣͞␤ T cell receptor (TCR) ؉ thymocytes were analyzed using TCR-transgenic (B10.D2 ؋ DO10)F 1 and (C57BL͞6 ؋ DO10)F 1 mice and Rag-1 ؊͞؊ ͞DO10 mice, which had been established by breeding and backcrossing between Rag-1 ؊͞؊ and DO10 mice. Almost all T cells from these mice were shown to bear V␣13͞V␤8.2 that is specific for chicken ovalbumin (cOVA) and restricted to I-A d . A normal proportion of the NK1.1 ؉ V␣13͞V␤8.2 ؉ thymocytes was generated in these mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Therefore, we consider the NK1.1-positive population of T cells we found in TCR-transgenic animals as a genuine NKT cell population. In line with such an interpretation, other groups have reported the presence of NKT cells in CD8 + TCR-transgenic mouse lines H-Y [36,37], BM3.3 [38,39] and 2C [40], as well as in the CD4 + TCR-transgenic mouse lines DO11.10 [41] and 3BBM74 [42]. Here, we extend the list of mouse lines bearing tgNKT cells to include OT-I and P14 (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Therefore, we consider the NK1.1-positive population of T cells we found in TCR-transgenic animals as a genuine NKT cell population. In line with such an interpretation, other groups have reported the presence of NKT cells in CD8 + TCR-transgenic mouse lines H-Y [36,37], BM3.3 [38,39] and 2C [40], as well as in the CD4 + TCR-transgenic mouse lines DO11.10 [41] and 3BBM74 [42]. Here, we extend the list of mouse lines bearing tgNKT cells to include OT-I and P14 (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…However, the mice analyzed in this study were unprimed and therefore have to be considered as antigen naive. Nonetheless, NK1.1 surface expression is probably not due to a general upregulation of NK1.1 on activated CD8 + T cells, as we never detected increased NK1.1 expression on transgenic CD8 + T cells after challenge with virally encoded antigen (ovalbumin-expressing adenovirus for OT-I) or soluble antigen (OVA 257-264 for OT-I and gp33 [33][34][35][36][37][38][39][40][41] for P14) in vitro or in vivo (data not shown). Schüler et al recently reported that thymic emigrants in neonates give rise to natural memory T cells with an activated phenotype [32], although the authors did not analyze the expression of NK1.1 on these cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations